Vpliv porodnih praks na porodno izkušnjo v institucionalni oskrbi - Prosen, Mirko (Obzornik zdravstvene nege, 2019)
Introduction: Pregnancy and childbirth are physiological events but in the present-day risk- oriented society they are often viewed as representing potential pathology and hazards. The aim of the study was to understand the experiences of childbearing women in institutional care through dominant childbirth practices which, in women's opinion, shaped their birth experience. Methods: Qualitative secondary analysis was used. The primary data was collected in 2014 in the study titled Medicalization of pregnancy and childbirth as social construction by using the narrative method. The sample in secondary analysis included 18 transcripts of the interviews conducted with women who had given birth in maternity hospitals. The analysis of qualitative data was conducted with the NVivo version 12 computer software. Results: In the analysis three themes were identified: (1) the importance of support of healthcare professionals and the autonomy in decision making; (2) a shift in focus of viewing Caesarean section as natural childbirth; (3) turning childbirth practices into routine and technical processes. Discussion and conclusion: Childbearing has always been guided by both, a negative and positive childbirth experience, so it is important to be familiar with both. For women, their first childbirth experience is a learning experience and at the same time a determining one, as it is the basis for determining their future childbirth experiences. The support of healthcare professionals and autonomy in decision making are crucial for a positive childbirth experience. In addition, changes in some of the established childbirth practices, which should follow evidence-based practice with a greater pace, would also contribute to a better experience of childbirth.
Keywords: babištvo; družba; medicalization; medicina; medicine; medikalizacija; midwifery; society; women; ženske